Health behavior of patients with ischemic heart disease - Paweł Węgorowski; Joanna Michalik; Rafał Zarzeczny; Renata Domżał-Drzewiecka; Grzegorz Nowicki (Kazimierz Wielki University, 2017)
Admission By analyzing the available scientific literature, it is possible to define ischemic heart disease as a set of disease symptoms that are a consequence of a chronic state of imbalance between the ability to supply nutrients and oxygen and the real need of myocardial cells for these substances. Adapting life-style behaviors to healthy living is a priority to prevent the onset and development of cardiovascular disease, especially ischemic heart disease, Purpose of research The aim of the study is to determine the health behavior of patients with ischemic heart disease. Materials and methods The study was conducted from 01.08.2015 to 28.12.2015 in a group of 35 people (15 women and 20 men). The research method used in the work is a diagnostic survey, the research technique used was a survey of its own author. Conclusions By analyzing the data collected, it is important to note that patients with coronary heart disease are often associated with health problems such as hypertension, diabetes and abnormal weight. The nutritional habits of the subjects studied can be described as abnormal, particularly the excessive intake of oily meat and too little fish intake. It has also been observed that most of the patients studied have familial predisposition to ischemic heart disease. Discussion Heart attacks occur mostly in people with obesity, diabetes and atherosclerosis. It is also closely related to ischemic heart disease. The health behaviors of patients suffering from Ischemic Heart Disease are moderately satisfactory and therefore the role of a nurse practitioner as a health educator is very difficult but essential in the prevention of ischemic heart disease.